후부다형각막이상증의 특징을 보이는 홍채각막내피증후군 - 나정호(Jeong Ho Na), 이효경(Hyo Kyung Lee) (Daihan angwa haghoi jabji, 2019)
목적: 후부다형각막이상증의 특징이 혼재된 홍채각막내피증후군 1예를 보고하고자 한다. 증례요약: 61세 여자 환자가 1년 전부터 시작된, 아침 기상 시 좌안의 찢어질 듯한 통증과 시야 흐림을 주소로 내원하였다. 초진 시시력은 양안 1.0이었고 안압은 정상이었다. 세극등검사상 우안 각막 중심부의 내피층에서 수평으로 주행하는 한 쌍의 평행한 선이, 좌안에서는 비스듬하게 주행하는 여러 쌍의 평행한 선이 관찰되었다. 띠 모양 병변은 좌안에서 더 두껍고 구불구불하였다. 내피세포병변 위의 각막은 깨끗하였고, 각막두께는 모두 정상 범위였다. 전방각경검사상 좌안에서만 국소적인 주변부 홍채 앞 유착이 관찰되었다. 홍채 및 동공은 양안 모두 정상이었다. 경면현미경검사상 우안은 각막내피세포의 크기가 커져 있었고 밀도가 668 cells/mm2로감소해 있었으며 좌안은 명암 반전이 뚜렷한 비정상적인 내피세포가 다수 관찰되었다. 결론적으로 본 증례는 후부다형각막이상증보다는 홍채각막내피증후군에 더 합당할 것으로 판단하였다. 결론: 후부다형각막이상증과 홍채각막내피증후군에서는 다수의 유사한 소견이 관찰될 수 있으므로 적절한 진단을 위하여 임상적 특징을 이해하는 것이 중요하다. Purpose: To report a case of iridocorneal endothelial syndrome, which overlapped with some of the features of posterior polymorphous corneal dystrophy. Case summary: A 61-year-old female presented with tearing pain and blurred vision in her left eye, which was aggravated in the morning. The symptom started approximately 1 year prior to her visit. At the initial visit, the visual acuities were 1.0 in both eyes and the intraocular pressures were normal. On slit-lamp examination, a single pair of horizontal parallel lines was observed at the central corneal endothelial layer in the right eye. In contrast, multiple pairs of oblique parallel lines were observed in the left eye. The lines of the lesions were more prominent and wavier in the left eye than those of the right eye. The overlying cornea was clear, and the corneal thicknesses were in the normal range in both eyes. Using a gonioscopic examination, localized peripheral anterior synechiae were observed only in the left eye. The pupil and iris were normal in both eyes. On specular microscopic examination, the corneal endothelial cell size in the right eye increased and the corneal endothelial density decreased to 668 cells/mm2. In the left eye, multiple abnormal endothelial cells with dark-light reversal were observed. In conclusion, the patient was subsequently diagnosed with iridocorneal syndrome, rather than posterior polymorphous corneal dystrophy. Conclusions: Posterior polymorphous corneal dystrophy and iridocorneal endothelial syndrome may present with many similarities. Therefore, in cases of uncertain diagnosis, an understanding of the clinical features is important for proper diagnosis. KCI Citation Count: 0